Wireless LAN : ATM interconnectivity - Qian, Qiang (2009)
A wireless LAN and Asynchronous Transfer Mode(ATM) interconnected system (internetworking) is proposed and analysed. Wireless LAN and ATM have been standardised by the IEEE802.il and the ITU-T committees, respectively. Wireless LAN reduces the problems involved in cabling within and across small and medium geographical areas of coverage. ATM is used as the common data transport technology for Broadband ISDN that is intended to support various services such as video, audio, image and data. It is a challenging issue to integrate wireless networks into the B-ISDN or construct a wireless Internet that allows each mobile individual to transmit multimedia data over broadband networks. The interconnected system enables the mobility functionality to be extended to the ATM network.